Gentianaceae endémicas del Perú - Castillo, Susy (2006)
The Gentianaceae are represented in Peru by 15 genera and nearly 170 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004; S. Castillo, pers. comm.), mainly herbs and shrubs. Here we recognize 103 endemic species in seven genera. Gentianella and Macrocarpaea are the genera with the largest number of endemic species. Endemic Gentianaceae are found in the Humid and Dry Puna, Paramo and Very Humid Montane Forests regions, between 1000 and 5100 m elevation. We applied IUCN categories and criteria to 99 species. Thirty-three endemic species have been found to date in Peruvian protected areas.